Analysis of Interest Read Libraries to Improve Student Learning Outcomes Man 9 Jombang - Moh Faridl Darmawan; Anita Yuni Arti (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The library as an institution that manages information sources should be used as the main key in the existing education and training process, both in the school environment, outside of school, the world of work and society in general. However, the reality is still far from expectations. Libraries are still not really popular in the community, this is indicated by the low interest in reading in the community and the lack of awareness that learning must find information or answers to the problems they face, namely by reading. This very low reading habit makes the ability of some students at school to be low. Therefore, the analysis of student library reading interest at MAN 9 Jombang. It is very necessary to find solutions in an effort to improve student learning. Because with a high enthusiasm for learning will spur very high achievement for students.